Analysis of a Newly Composed Cu-Al-Mn SMA ShowingAcute SME Characteristics - Karaduman, O.; Canbay, C. Aksu; Unlu, N.; Ozkul, I (Amer Inst Physics, 2019)
In this research study,the Cu-based shape memory alloy (SMA) with a new57.53Cu-37.78Al-4.69Mn (at%)composition was prepared by arc melting.The alloy obtained as-castingot was homogenized at 900 degrees C and rightafter quenched in iced-brine water to get the formation of beta 1' martensite structure in the alloy, which is a very common process. Then the samples cut from that ingot were examined by taking calorimetric and microstructural measurements. The results of the differential calorimetric analysis (DSC) measurements as cycled heating/cooling hysteresis curves showed the characteristic back and forward martensitic phase transition peaks, such that, they have become very deep (or high) and sharp (i.e. the temperature gaps between start and finish points of both way transitions are narrow). These indicated that this newly composed SMA has a fast and acute shape change ability. Thermodynamical parameters like entropy change values of transitions and hysteresis temperature were calculated by using DSC data. Differential thermal analysis (DTA) measurement of the alloy was also carried out and this thermographed the high temperature behavior of the alloy. The XRD analysis of the alloy sample at room temperature provided the microstructural information as diffraction peaks and corresponding miller indices which alluded the existing martensite forms in the alloy. The valence electron concentration (per atom) of the alloy was also determined. From all mutually reinforcing results, it was concluded that the SMA with thisunprecedented composition can be used as one of the alternatives in many SMA applications.
35th International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 04-08, 2019 -- Bodrum, TURKEY
Keywords: Shape-Memory Alloys; Martensitic-Transformation; Microstructure